Serum IL-33 Levels Are Associated with Liver Damage in Patients with Chronic Hepatitis C. (2nd November 2011) - Wang, Juan; Zhao, Pingwei; Guo, Hui; Sun, Xiguang; Jiang, Zhenyu; Xu, Lijun; Feng, Junyan; Niu, Junqi; Jiang, Yanfang
Abstract : Interleukin-33 (IL-33) is associated with the development of Th2 responses. This study examined the potential role of IL-33 in the pathogenic process of chronic hepatitis C (CHC) in Chinese patients. The levels of serum IL-33 and sST2 in 154 patients with CHC, 24 with spontaneously resolved HCV (SR-HCV) infection and 20 healthy controls (HC), were analyzed by ELISA. The concentrations of serum IL-2, IFN- γ, TNF- α, IL-4, IL-6, and IL-10, HCV loads, ALT, AST, and HCV-Ab were measured. We found that the levels of serum IL-33 in CHC patients were significantly higher than those of SR-HCV and HC but decreased after treatment with interferon for 12 weeks. More importantly, the levels of serum IL-33 were correlated with the concentrations of ALT and AST in CHC patients. The levels of serum sST2, as a decoy receptor of IL-33, were significantly higher in CHC and SR-CHC patients than those in HC, and there was no correlation between the levels of serum sST2 and IL-33. The concentrations of serum IFN- γ and IL-6 in CHC patients were significantly lower than those of SR-HCV. These data suggest that IL-33 may be a pathogenic factor contributing to CHC-related liver injury.